Molecular nature of allelic polymorphism of highly variable microsatellite locus Du161(arm) in unisexual lizard Darevskia armeniaca (lacertidae) - Malysheva, D. N.; Korchagin, V. I.; Tokarskaya, O. N.; Ryskov, A. P. (Russian journal of genetics, 2012)
In the genome of unisexual (parthenogenetic) lizard Darevskia armeniaca , highly variable locus Du161 ( arm ) was discovered. Analysis of allelic polymorphism was carried out using locus-specific PCR of the lizard DNA specimens from 13 isolated Armenian populations ( N = 138). In the sample examined, a total of 12 Du161(arm) alleles were identified, and their differences at the level of primary DNA structure were determined. Sequence analysis of the Du161(arm) alleles showed that their microsatellite clusters contained repeats of one type (GATA repeats). Allelic Du161(arm) variants differed in the number of GATA monomers in microsatellite, point mutations of transition and transversion types, located at fixed distances from micro-satellite cluster, and by single nucleotide insertions, as well as by longer insertions located within and outside of the microsatellite cluster. Moreover, point mutations formed different combinations (haplotypes), typical of certain alleles. These combinations can be used for the analysis of the origin and inheritance of these alleles in D. armeniaca , as well as for investigation of their interspecific variation in the representatives of the genus Darevskia .